High-yield paper-based quantitative blood separation system. Issue 24 (16th November 2018) - Lu, Zhengda; Rey, Elizabeth; Vemulapati, Sasank; Srinivasan, Balaji; Mehta, Saurabh; Erickson, David
Abstract : HYPER platform: affordable whole blood separation with unique cross-flow filtration that makes rapid diagnostics at point-of-care available. Abstract : Interest in developing paper-based devices for point-of-care diagnostics in resource-limited settings has risen remarkably in recent decades. In this paper, we demonstrate what we refer to as "high yield passive rrythrocyte removal" (HYPER) technology, which utilizes capillary forces in a unique cross-flow filtration for the separation of whole blood with performance comparable to centrifuges. As we will demonstrate, state-of-the-art passive blood separation methods implemented in paper-based systems exhibit rapid blood cell clogging on the filtration media or serum outlet and yield only about 10–30% of the total serum present in the sample. Our innovation results from the inclusion of a differentiation pad, which exploits hydrodynamic effects to reduce the formation of a fouling layer on the blood filtration membrane resulting in more than 60% serum yield with undiluted whole blood as direct input. To demonstrate the effectiveness of the HYPER technology we implement it in a lateral flow system and demonstrate the accurate quantification of vitamin A and iron levels in whole blood samples in 15 minutes.